Euralexova konferenca v Torinu, 2006 - Hočevar, Mojca M. (Mostovi (Ljubljana), 2006)
At the latest conference of the European Association for Lexicography, which took place in Turin in September 2006, lexicographers and researchers of language fields dealt with different lexicographic topics that are briefly presented in this report.
Keywords: konference; poročila; raziskovanje; slovaropisje